2018
DOI: 10.4149/neo_2018_171206n801
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of long noncoding RNA CCAT1 inhibits cell growth, invasion and peritoneal metastasis via downregulation of Bmi-1 in gastric cancer

Abstract: Long noncoding RNA colon cancer-associated transcript 1 (lncRNA CCAT1) is highly expressed in gastric cancer (GC) tissues compared with normal counterparts and CCAT1 upregulation can promote proliferation and migration of GC cells in vitro. B-cell specific moloney leukemia virus insertion site 1 (Bmi-1) expression is positively correlated with tumor progression. The present study aimed to investigate the biological functions of CCAT1 and the relationships between CCAT1 and Bmi-1 in GC progression. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…Examination of the expression of lncRNAs during TNF- α induced osteogenic differentiation revealed 58 upregulated and 19 downregulated lncRNAs on day 7 and 73 upregulated and 60 downregulated lncRNAs on day 14 [ 181 ]. lncRNA colon cancer-associated transcript 1 (CCAT1) is initially discovered to participate in metabolic, migratory, and proliferative processes in some cancers [ 182 ]. Later on, it was found that CCAT1 can promote the proliferation and odontogenic differentiation of DPSCs.…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…Examination of the expression of lncRNAs during TNF- α induced osteogenic differentiation revealed 58 upregulated and 19 downregulated lncRNAs on day 7 and 73 upregulated and 60 downregulated lncRNAs on day 14 [ 181 ]. lncRNA colon cancer-associated transcript 1 (CCAT1) is initially discovered to participate in metabolic, migratory, and proliferative processes in some cancers [ 182 ]. Later on, it was found that CCAT1 can promote the proliferation and odontogenic differentiation of DPSCs.…”
Section: Epigenetic Mechanisms In Dpscsmentioning
confidence: 99%
“…Overexpression of CCAT1 has been observed in colorectal cancer, where it promotes tumor growth and metastasis [22, 23]. Similarly, CCAT1 is overexpressed in gastric cancer tissue and is associated with tumor progression [24, 25]. One study has demonstrated an association between CCAT1 and both overall and progression-free survival in breast cancer [26].…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al reported that CCAT1 was significantly upregulated in nasopharyngeal carcinoma (NPC) tissues and that CCAT1 induced growth, migration and invasion and inhibited apoptosis in NPC cells [30]. Li et al also found that CCAT1 was highly expressed in gastric cancer (GC) tissues compared with normal counterparts and that CCAT1 upregulation promoted proliferation, invasion and migration of GC cells in vitro [31]. Another study demonstrated that CCAT1 was significantly upregulated in multiple myeloma (MM) tissues and cell lines and that CCAT1 knockdown significantly inhibited cell proliferation, induced cell cycle arrest at the G0/G1 phase, promoted cell apoptosis in vitro, and suppressed tumor growth in vivo [32].…”
Section: Discussionmentioning
confidence: 99%